THOUGHT STOPING AND GUIDED IMAGERY THERAPY EFFECTS ON ANXIETY LEVEL OF THIRD TRIMESTER PRIMIGRAVIDA PREGNANT WOMEN - Yuliani Budiyarti (LPPM Universitas Sari Mulia, 2021)
Background: The first pregnancy can cause psychological problems, namely anxiety, if left untreated it will have a negative impact on both the mother and the fetus. Actions to reduce anxiety include thought stopping and guided imagery. The purpose of this study was to analyze the effect of Tought Stopping and Guided Imagery therapy on the anxiety level of third trimester primgravida pregnant women in the New Basirih Health Center area. Method: This type of research is quantitative with a non equivalent control group design pretest-posttest. The study population was all third trimester primigravida pregnant women in the Puskesmas Basirih Baru area. The research samples were 20 trimester primigravida pregnant women, divided into thought stopping intervention and guided imagery groups with total sampling technique. Instruments for measuring anxiety, namely HRS-A, Wilcoxon and Mann Whitney test analysis. Results: Thought stopping statistic result p-value = 0.005 and guided imagery statistic result p-value = 0.007 so both has affected the anxiety level of pregnant women. Conclusion: Thought stopping and guided imagery can be used by pregnant women to reduce anxiety levels. Keywords: Anxiety Level, Guided Imagery, Thought Stopping.